The Impact of Employee Characteristics in the Relation of Financial Knowledge, Financial Management Behavior and Personal Income with Investment Decision of Employee - Natasha Asmara; Andreas Lako; Eny Trimeiningrum (Soegijapranata Catholic University, 2020)
The resarch is to analyze the impact of financial knowledge, financial management behavior, and personal income on investment decision of the employees of PT. Industri Jamu dan Farmasi Sido Muncul Tbk. This study is also to analyze moderating effect of employee’ characteristics in relation to financial knowledge and financial management behavior and personal income to investment decision of the employees. Based on purposive sampling and questionnaire, the study results in financial knowledge, financial management behavior, and personal income have positive impact on investment decision of the employees. However, employee’ characteristics do not show moderating effect in relations to financial knowledge and management behavior and personal income to investment decision of the employees. The results inidicate that emloyees’ characteristics (risk taker or risk adverse) weaken the influence of financial knowledge, financial management behavior, and personal income to investment decision of the employees.